PENGEMBANGAN MODUL PRAKTIKUM UNTUK PERBANDINGAN UNJUK KERJA SUMBER CAHAYA OPTIK LED DAN LASER DALAM SISTEM KOMUNIKASI OPTIK - Utari Yulianingsih, Ni Komang; Sudiarta, Pande Ketut; Putra Sastra, Nyoman (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p20, 2021)
LED optical light source and laser diode function as an information carriers in the optical communication systems. Each optical light source in the form of LED, CW Laser, and VCSEL Laser has advantages and disadvantages. Based on these advantages and disadvantages, a study was carried out on the internal and external characteristics of optical light sources to determine the optimal optical light source to use as needed. Simulations are carried out in optical system software. The performance analyzed is Q-Factor, BER, and Eye Diagram until it reaches the ITU-T G.984.2 standard with a minimum limit of Q-Factor = 6 and BER = 10-9. The feasibility test of the practicum module uses the method of filling out a questionnaire with a Likert scale of 1–5 and giving pre and post-test to the practitioner. The results of this study were an increase in the internal characteristics of the LED, a decrease in the signal power of the CW Laser, and an increase in the bias current of the VCSEL Laser resulting in a decrease in Q-Factor, and an increase in the BER value. The comparison of the increase in bit rate and transmission distance showed that CW Laser can transmit a higher bit rate and a longer transmission distance. The comparison of the transmission distance that can be covered by each optical light source shows that the CW Laser travels the farthest transmission distance . Increased understanding of the practitioner based on the post-test score which is higher than the pre-test score can be used as the basis that this practicum module as a whole is very suitable for use as teaching material. This is also supported by the feasibility test of the questionnaire filling method with a Likert scale of 1-5 with a percentage of the practitioner's assessment of 88.6%.